Presenting a Model of Social Media Influence in Combating Parental Violence Against Children - Ali Abdulwahid Alobaidi, Anas; Atrian, Narges; Falah Zaeid Almashkheel , Haider; Aghajani, Mojtaba (Assessment and Practice in Educational Sciences, 2025)
The present study aimed to design and explain a model of social media influence in combating domestic violence against children and its role in modifying and changing parental behavior. Utilizing a qualitative approach and grounded theory methodology based on Strauss and Corbin’s paradigm model, this study sought to identify the discursive, contextual, intervening, and strategic components influencing parental behavior in response to media content related to domestic violence. The research population consisted of parents with experience using social media to gain awareness about children’s rights and parenting issues. Data were collected through semi-structured interviews with 13 experts and specialists and analyzed using open, axial, and selective coding techniques. Findings indicated that social media, through experiential narratives, emotional messaging, real-life imagery, and advocacy campaigns, plays a significant role in enhancing empathy, sensitivity, and parental reflection on their own behaviors. The resulting model revealed that parental attitude and behavior change does not occur directly but through a chain of causal factors (e.g., history of exposure to violence), contextual factors (e.g., media literacy level and social status), intervening factors (e.g., counseling services and social support), strategic factors (e.g., parental engagement in sharing and online discussions), and consequential factors (e.g., changes in parenting style). This model can serve as a foundation for developing educational, counseling, and media-based programs to address domestic violence against children.